Nationalism: what we know and what we still need to know - Mylonas, H; Tudor, M (Annual Reviews, 2021)
Amid the global resurgence of nationalist governments, what do we know about nationalism? This review takes stock of political science debates on nationalism to critically assess what we already know and what we still need to know. We begin by synthesizing classic debates and tracing the origins of the current consensus that nations are historically contingent and socially constructed. We then highlight three trends in contemporary nationalism scholarship: (a) comparative historical research that treats nationalism as a macropolitical force and excavates the relationships between nations, states, constitutive stories, and political conflict; (b) behavioral research that uses survey data and experiments to gauge the causes and effects of attachment to nations; and (c) ethnographic scholarship that illuminates the everyday processes and practices that perpetuate national belonging. The penultimate section briefly summarizes relevant insights from philosophy, history, and social psychology and identifies knowledge gaps that political scientists are well-positioned to address. A final section calls for more comparative, cross-disciplinary, cross-regional research on nationalism.